ECM: A Precision Machining Process for the 21st Century - Gandhi, Sidharth (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 11 No 3&4 (2024): Journal of Advanced Research in Instrumentation and Control Engineering, 2025)
This research article provides an in-depth analysis of Electrochemical Machining (ECM), an innovative non-conventional machining technique known for its remarkable capacity to effectively produce complex shapes and components with unmatched precision and surface quality. By using electrochemical dissolution, ECM demonstrates exceptional performance in the machining of rigid and fragile materials, making it an essential method in contemporary production. The present study documents the progression of ECM, clarifies its benefits and constraints, and investigates new advancements in process optimisation and parameter improvement. Moreover, it analyses the combined incorporation of electrical conductivity materials (ECM) with advanced technologies and emphasises current research efforts aimed at enhancing sustainability and efficiency. Through a comprehensive analysis of the capabilities and constraints of ECM, this study is an essential reference for academics and industry experts aiming to fully use the promise of this adaptable machining method.